UTILIZATION OF WATER HYACINTH PLANTS (EICHORNIA CRASSIPES), JASMINE WATER (ECHINODORUS PALEAFOLIUS) AND APU WOOD (PISTIASTRATIOTES) ON DECREASING LEVEL OF LIQUID WASTE POISONOUS OF TOFU - Fadhillah, Wiznie; Purba, Edison; Elfiati, Deni (Journal of Community Research and Service, 2017)
Abstract The aim of this research was to improve the quality of liquid waste water by looked at the role of test plants (warter hyacinth, water jasmine and apu wood)by phytoremediation process in reducing pollutant level. This research was conducted at Rumah Kaca Faculty of Agriculture University of Sumatera Utara Medan from July 2016 to April 2017.This research was used factorial randomized block design with two factors. The first factor was tofu waste with three levels; L0 (no waste) as control , L1(25%) and L2 (50%). The second factor was plant species with four levels were T0 (no plant as control), T1 (water hyacinth), T2 (jasmine water) and T3 (apu wood). The parameters observed were BOD (mg / L), COD (mg / L), TSS (mg / L), NH3N (mg / L), pH, waste colours, odor waste and dry weight of plans (grams).The results showed that the three test plants could be used for phytoremediation process, tofu waste, 25% waste concentration as the best apu wood in reducing the pollutant level of tofu waste.Keywords: tofu liquid waste, aquatic plants, phytoremediation, contaminants